"Right now we are scared of each other, we fear everyone, the whole world has COVID": The impact of COVID-19 on young female sex workers in Kampala, Uganda, during national lockdowns in 2020-2021. - Rachel King; Ritah Namugumya; Catherine Namuddu; Femke Bannink Mbazzi; Francis Xavier Kasujja; Judith Nankabirwa; Janet Seeley (PLOS Global Public Health, 2023)
In 2020-2021 the COVID-19 pandemic led to multiple and diverse global public health response strategies globally and in Uganda to slow the spread of the virus by promoting wearing face coverings in public, frequent hand washing, physical distancing, restricting travel, and imposing home lockdowns. We conducted 146 interviews over four rounds of phone-follow up calls over 15 months with 125 young female sex workers coinciding in time with four different government-imposed lockdown periods in Kampala, Uganda, to assess the impact of these measures on young sex workers, their families and their communities as well as to gauge their resilience. Our findings revealed how COVID-19 fears and public health restrictions over time pushed an already marginalized population to the brink and how that pressure drove some participants into a new way of life.